Investigation of low‐disturbance seismic retrofit method for steel column bases using curved members - Kun‐Sian Lin; Masahiro Kurata; Yutaro Kawasaki; Yoshio Kitatani (Japan Architectural Review)
Abstract Seismic retrofit has always been a very important subject in recent years. However, typical retrofit techniques such as load‐resisting systems, damper devices, and seismic isolation systems will cause considerable disturbances to the structural system, such as increased force demand, and the building's occupants will need to be temporarily relocated during the construction. A design of the low‐disturbance retrofit method for steel column bases that uses the advantages of the curved member has been proposed in the study to improve seismic performance and reduce the mentioned demerits above. The basic mechanism of the curved member retrofit system was first analytically evaluated by preliminary modeling, followed by a parametric study to verify the effective shape. Four curved member specimens were tested with variations in fabrication processes and boundary conditions. Several aspects, including overall behavior, strength backbones, and deformation shapes of the specimens, were examined upon measured responses. The hysteretic performance of the curved member retrofit system is verified to achieve a stable cyclic behavior with limited strength degradation. A set of physical equations for estimating the lateral loads were established and verified by developing numerical models with a good agreement that enabled them to accurately represent the measured responses in the test.